EFFECTIVENESS OF CUSTOMARY DISPUTE RESOLUTION THROUGH CUSTOMARY COURTS: A STUDY IN LAWE SEMPILANG VILLAGE, LAWE ALAS DISTRICT - Ebi Purnama; Muhammad Syuib; Azmil Umur (Justisi: Jurnal Ilmu Hukum, 2025)
The Authority of Customary Court Institutions in Settling Disputes through Customary Courts is one of the Alternatives in resolving disputes. Customary courts generally accommodate the interests of the disputing parties in the customary law area that applies both in civil law and criminal law that are resolved through customary courts are acts that violate Customary Norms. This study is related to customary court decisions that were not implemented in Lawe Sempilang Village, Lawe Alas District, Southeast Aceh Regency. This study aims to determine how the process of resolving customary disputes through customary justice: A study in Lawe Sempilang Village, Lawe Alas District, Southeast Aceh Regency. This type of research is empirical legal research (field research) research that studies phenomena in its natural environment with a sociological legal approach. Data collection techniques through interviews, observations and documentation. While the analysis technique uses qualitative descriptive methods. The results of the study indicate that customary justice has not been effectively used in Lawe Sempilang Village, Lawe Alas District, Southeast Aceh Regency with other required provisions in the form of replacement money/fines to perpetrators who are proven guilty and if the perpetrator is unable to pay, the victim can report to the police and sue in public court.